Prospects for the Development of Organic Vegetable Agribusiness in North Oba Subdistrict, Tidore Kepulauan City - Djumadil, Nurdiyanawati; Mahmud, Haris; Syafie, Yunus (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
This study was carried out at the Gapoktan Timamo, West Ternate District, Ternate City, from May to October 2024. A survey using qualitative and quantitative methods was used in this study. The observed variables were indicators/criteria and selection of alternative strategies regarding the prospect of developing organic vegetable agribusiness. The Analytical Hierarchy Process (AHP) was used to analyze the data. The AHP results showed that there was inconsistency value based on the criteria for production facilities provider, subsystem production subsystem, marketing subsystem, and supporting institutional subsystem in prospects for organic vegetable development and based on prospect alternatives for organic vegetable development as a whole, which means that the analysis results were acceptable. The agribusiness subsystem criteria in the prospect of developing organic vegetable agribusiness as a whole, the most influential was the marketing subsystem with a weight value of 0.351. Marketing is an important part which connects production and consumption activities.